2008
DOI: 10.1002/sim.3489
|View full text |Cite
|
Sign up to set email alerts
|

Working‐correlation‐structure identification in generalized estimating equations

Abstract: Selecting an appropriate working correlation structure is pertinent to clustered data analysis using generalized estimating equations (GEE) because an inappropriate choice will lead to inefficient parameter estimation. We investigate the well-known criterion of QIC for selecting a working correlation structure, and have found that performance of the QIC is deteriorated by a term that is theoretically independent of the correlation structures but has to be estimated with an error. This leads us to propose a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
148
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 16 publications
4
148
0
1
Order By: Relevance
“…For example, Pan (2001a) proposed a modification of Akaike's information criterion (AIC), called the "quasi-likelihood under the independence model criterion (QIC)." In addition, Hin and Wang (2009) proposed a correlation information criterion (CIC) that modifies the QIC and substantially improves its performance.…”
mentioning
confidence: 99%
“…For example, Pan (2001a) proposed a modification of Akaike's information criterion (AIC), called the "quasi-likelihood under the independence model criterion (QIC)." In addition, Hin and Wang (2009) proposed a correlation information criterion (CIC) that modifies the QIC and substantially improves its performance.…”
mentioning
confidence: 99%
“…In the present study, the models were fit with the working correlation matrix structures: autoregressive, uniform, independent and unstructured. The choice was made using the correlation information criterion (CIC) proposed by Hin and Wang (2009), considering that the correlation matrix with the lower CIC is the most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical analyses were performed with the aid of R statistical software (R DEVELOPMENT CORE TEAM, 2011), and the gee (CAREY et al, 2012) and geepack packages (HØJSGAARD et al, 2006;YAN, 2002;YAN;FINE, 2004) were used to fit the GEE models.…”
Section: Discussionmentioning
confidence: 99%
“…GEEs provide consistent parameter and standard error estimates even if the correlation structure among responses is not specified correctly. However, Hin and Wang (2009) and Wang and Carey (2003) showed that the misspecification of working correlation structure may cause inaccurate results of the parameter estimates especially in small sample sizes. 9,10 Besides the GEEs, generalized linear mixed model (GLMM) provides a flexible approach to handle longitudinal data from exponential family distributions (normal, binomial or Poisson) by using link functions.…”
mentioning
confidence: 99%
“…However, Hin and Wang (2009) and Wang and Carey (2003) showed that the misspecification of working correlation structure may cause inaccurate results of the parameter estimates especially in small sample sizes. 9,10 Besides the GEEs, generalized linear mixed model (GLMM) provides a flexible approach to handle longitudinal data from exponential family distributions (normal, binomial or Poisson) by using link functions. GLMM is an extension of generalized linear models including the random effects, which represents the influence of each subject on his/her own repeated responses.…”
mentioning
confidence: 99%